Hubungan Pola Makan dengan Kejadian Obesitas Anak pada Anak SD Diniyyah Al-Azhar Jambi - Hannaya Putri; Raihanah Suzan; Miftahurrahmah Miftahurrahmah (Journal of Medical Studies, 2023)
ABSTRACT Background: Based on the results of Riskesdas Jambi Province in 2018, Jambi City has the fourth highest prevalence of childhood obesity out of 34 provinces in Indonesia at 11.4%. The existence of an unbalanced diet can cause an energy imbalance in the body which causes obesity. The purpose of this study was to determine the relationship between diet and the incidence of childhood obesity in children. SD Diniyyah Al-Azhar Jambi. The purpose of this research was to determine the relationship between dietary habits and the incidence of childhood obesity in elementary school children in Diniyyah Al-Azhar Jambi. Methods: This research is a type of analytical research using a cross-sectional design. Data analysis was carried out to test the hypothesis by using the Chi-Square test. Results: there are many obesity cases (54.3%) and there are many unbalanced eating habits (57.6%). The results of the statistical analysis of eating habits (p-value 0.001) with obesity in children show a strong relationship. Conclusion: The results of the statistical analysis of eating patterns (p-value 0.001) with obesity in children show a strong relationship. Keywords: Obesity, Dietary habits, Children ABSTRAK Latar belakang: Berdasarkan hasil Riskesdas Provinsi Jambi tahun 2018, Kota Jambi menduduki prevalensi obesitas anak tertingi keempat dari 34 provinsi di Indonesia sebesar 11,4%. Adanya pola makan yang tidak seimbang dapat menyebabkan ketidakseimbangan energi dalam tubuh yang menimbulkan obesitas.Tujuan penelitian ini adalah untuk mengetahui hubungan antara pola makan dengan kejadian obesitas anak pada anak SD Diniyyah Al-Azhar Jambi. Penelitian ini bertujuan untuk mengetahui hubungan pola makan dengan kejadian obesitas anak pada anak SD Diniyyah Al-Azhar Jambi. Metode: Penelitian ini merupakan jenis penelitian analitik dengan menggunakan desain cross sectional. Analisis data dilakukan untuk menguji hipotesis dilakukan dengan uji Chi- Square. Hasil: Ditemukan banyak kejadian obesitas (54,3%) dan banyak pola makan tidak seimbang (57,6%). Hasil analisis statistik pola makan (p-value 0,001) dengan obesitas pada anak menunjukan hubungan yang kuat. Kesimpulan: Ada hubungan yang bermakna antara pola makan dengan kejadian obesitas anak pada anak SD Diniyyah Al-Azhar Jambi. Kata kunci: Obesitas, Pola Makan, Anak